2016
DOI: 10.1103/physrevc.93.055802
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of the isospin-asymmetry expansion of the nuclear equation of state in many-body perturbation theory

Abstract: The isospin-asymmetry dependence of the nuclear matter equation of state obtained from microscopic chiral two-and three-body interactions in second-order many-body perturbation theory is examined in detail. The quadratic, quartic and sextic coefficients in the Maclaurin expansion of the free energy per particle of infinite homogeneous nuclear matter with respect to the isospin asymmetry are extracted numerically using finite differences, and the resulting polynomial isospinasymmetry parametrizations are compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 58 publications
6
78
0
Order By: Relevance
“…2 the neutron matter thermodynamic equation of state (the free energy per particle as a function of temperature and density) obtained from the n3lo414 chiral two-and three-body potentials. The results are in good agreement with previous studies, 37,38 which employed the same two-and three-body potentials but included also self-consistent Hartree-Fock single-particle energies in the second-order diagrams. As we will show later, second-order perturbative contributions to the neutron matter equation of state and the chiral condensate are relatively small.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…2 the neutron matter thermodynamic equation of state (the free energy per particle as a function of temperature and density) obtained from the n3lo414 chiral two-and three-body potentials. The results are in good agreement with previous studies, 37,38 which employed the same two-and three-body potentials but included also self-consistent Hartree-Fock single-particle energies in the second-order diagrams. As we will show later, second-order perturbative contributions to the neutron matter equation of state and the chiral condensate are relatively small.…”
Section: Resultssupporting
confidence: 82%
“…We start from a coarse-resolution chiral potential 34,35 with a momentum-space cutoff of Λ = 414 MeV, which has been shown to exhibit good convergence properties [34][35][36][37][38] in many-body perturbation theory calculations of infinite nuclear matter, comparable to low-momentum potentials constructed via renormalization group methods. 16,[39][40][41] In the present calculation the free energy per particle of pure neutron matter at finite temperature is computed in the imaginary-time Matsubara formalism.…”
Section: Neutron Matter At Finite Temperature From Many-body Perturbamentioning
confidence: 99%
“…[30] together with the binding energies of doubly closed shell nuclei. We define the χ 2 minimization function:…”
Section: Nuclear Modelmentioning
confidence: 99%
“…Indeed, the quartic contribution to the kinetic symmetry energy contributes 5T/243=0.021T, about 2/3 of the missing amount. Most theoretical calculations of the potential contribution to the symmetry energy also find only small corrections beyond the quadratic term (Carbone et al 2014;Wellenhofer et al 2016). Recent calculations of neutron-rich matter (Drischler et al 2016b) have shown that up to densities approaching u∼1.5 the quadratic assumption is accurate to better than 1 MeV in the symmetry energy per particle for all values of x.…”
Section: E U X E U S U X S U Xmentioning
confidence: 99%
“…Studies suggest that these terms are small (Carbone et al 2014;Wellenhofer et al 2016). If the energy is divided into kinetic and potential contributions, then the kinetic energy of degenerate noninteracting fermions can be expanded as E u x m n u x x , 3 5 2 3 1 3 kin 2 2 0 2 3 5 3 5 3 …”
Section: E U X E U S U X S U Xmentioning
confidence: 99%